Translanguaging in Multilingual Classrooms: A Phenomenological Study on Teachers’ and Students’ Perceived Benefits and Challenges in Relation to Student Participation Among Grade 12 Students - Princess Yasmien G. Yago; Keira Elize Belle A. Agpaoa; Jasmine A. Diata Cruz (Journal of Research in Education and Pedagogy, 2026)
This study examined the use of translanguaging in a multilingual senior high school classroom and explored how teachers and students perceive its benefits and challenges in relation to student participation. Grounded in the context of the Philippine senior high school setting, the research focused on Grade 12 Humanities and Social Sciences (HUMSS) students at Ilocos Norte National High School, Laoag City, Ilocos Norte, Philippines, during the first semester of the academic year 2024–2025. Using a phenomenological design, the study aimed to capture the lived experiences of participants regarding translanguaging practices in the classroom. Six participants were purposively selected, consisting of three HUMSS teachers and one student under each teacher. Data were collected through a validated structured interview guide and analyzed using thematic analysis. Findings revealed five major themes describing the perceived benefits of translanguaging: Cognitive and Academic Enhancement Supporting Classroom Participation, Affective Development and Confidence Building, Active Participation and Engagement, Inclusive and Equitable Learning Environment, and Language Development and Skills for Classroom Participation and Future Readiness. These findings indicate that translanguaging supports deeper understanding, strengthens confidence, increases classroom participation, promotes inclusivity, and enhances academic language skills. However, three major themes emerged regarding challenges: Linguistic Barriers and Code-Switching Difficulties, Challenges with Technical and Academic Terminology, and the Need for Guidance and Pedagogical Support. These findings suggest that while translanguaging enhances participation, its implementation requires intentional scaffolding and institutional support. Implications highlight the need for structured teacher training, supportive school policies, and deliberate classroom strategies to maximize the perceived benefits of translanguaging in multilingual educational settings.